THE ‘PADLET’ APPLICATION AS A LEARNING MEDIA TOOL FOR IMPROVING WRITING SKILLS: STUDENTS’ POINT OF VIEW - Lubis, Nursyahrina; Rafida, Tien (TELL - US JOURNAL, 2025)
Technological advancements significantly affect language learning making it more effective and accessible. The research aims to investigate students' perceptions on the use of the Padlet application in learning writing skills. The research used a qualitative case study approach method, involving 8th grade students of junior high schools in Medan. Data were collected using questionnaires and semi-structured interviews, for questionnaires involving 31 students and interviews involving 5 students who had completed the questionnaires. Participants were selected using the purposive sampling method. The percentage results from the questionnaire provided insight into students' perceptions, the interviews added to the understanding of students' learning experiences in using Padlet. The results showed that most students gave positive perceptions of Padlet as a learning media tool to improve students' writing skills, namely, ease of access and usability, effectiveness in improving writing skills, motivation in improving writing skills, and challenges in using the Padlet application. Therefore, Padlet application is recommended as an effective writing learning media tool used in the classroom. However, it is suggested that further research can involve a larger number of participants so as to gain a more comprehensive insight into students' perceptions of using Padlet, further researchers can also focus more on other language skills.